A Review on Talas Beneng (Xanthosoma undipes K. Koch) and Its Role in Food Security - Gisti Rahmawati; Fakhera Shofwa; Siti Ameilia Kurniasih (Jurnal Biologi Tropis, 2026)
Talas beneng (Xanthosoma undipes K. Koch), a tuber crop originating from Pandeglang Regency, Banten, represents a promising staple carbohydrate alternative. This literature review aims to examine the potential of talas beneng as a locally based food resource in supporting food diversification and food security. This study employed a narrative literature review with a structured search approach to evaluate the potential of talas beneng as a locally based food resource. Relevant scientific publications published between 2001 and 2025 were identified through databases such as Google Scholar and national journal portals, and were selected based on their relevance to nutritional characteristics, agronomic performance, and processing potential. The findings indicate that talas beneng has high nutritional value, including dietary fiber, protein, carbohydrates, vitamins, and minerals, along with a low glycemic index of approximately 55%. Agronomically, talas beneng grows well in mountainous areas, exhibits resistance to pests and diseases, and produces high tuber yields. Moreover, talas beneng can be processed into various food products, such as flour, snacks, and bakery products, thereby enhancing its utilization and economic value. Overall, the reviewed literature suggests that talas beneng holds strong potential as a local food resource and could play a strategic role in supporting sustainable food security when accompanied by further research, community education, institutional collaboration, and improved access to processing technologies.